Development of Illustrated Story Books for Anti-Corruption Education in Early Childhood - Putri, Mayra Amanda; Masykuroh, Khusniyati (Edukasi, 2025)
This study was aimed to develop effective picture storybooks for instilling anti-corruption values in early childhood. Research and Development (R&D)  was used in this study. This study developed illustrated storybooks as learning media to instill anti-corruption character values in early childhood using the ADDIE method. This research was conducted at an early childhood education institution in South Jakarta. The study involved three participants;   principals and   teachers of kindergarten. Interview was used in  analysis phase. During the development phase, three illustrated storybooks conveying messages of honesty, care, and responsibility were created. Expert validation result indicated that the books are suitable for use as learning media. Implementation in the early childhood institutions received positive responses from teachers and principals, indicating the books’ effectiveness in instilling anti-corruption character values. The study recommends developing diverse learning media, providing teacher training, and involving parents to support anti-corruption character education from an early age. The findings demonstrate that illustrated storybooks serve as effective media for promoting the learning of anti-corruption values in early childhood.